Infecciones asociadas al cuidado de enfermería en el área de medicina interna. Hospital General IESS Babahoyo. periodo noviembre 2023- abril 2024. - Ramírez Alcívar, Wendy Yomaira (2024)
Objective: Identify infections associated with nursing care in the internal medicine area of the IESS Babahoyo General Hospital, November 2023- April 2024. Methodological design: In this research we will work with a population of 50 patients from the internal medicine area of the IESS Babahoyo General Hospital in the period November 2023-April 2024, revealing the infections associated with nursing care. The instrument of choice for this research project will be the registration form for notification of events related to patient safety of the Ministry of Public Health (MSP), it consists of eight topics and in each topic an item is moved which will focus on the analysis and notification of infections associated with nursing care in the internal medicine area. Results: The research on the identification in the prevention and control of infections associated with nursing care at the IESS Babahoyo General Hospital involved 10 nursing graduates. A lack of uniformity was found in internal communication, with 40% of respondents uninformed, and 40% not following established guidelines. Furthermore, although the majority receive periodic training, 30% do not. Key areas for improvement were identified, such as internal communication, adherence to protocols and staff training. These findings are essential to implement effective interventions and improve patient and staff safety in the hospital. Conclusions: The detailed analysis of infections related to nursing practice highlights their complexity and urgency to address them in the health field. These infections represent a clinical and epidemiological challenge, as well as a threat to patient safety and the sustainability of the health system. Adherence to prevention protocols is crucial, and continuous training of staff is essential to minimize the risk of infections. Risk factors, from poor hygiene to antimicrobial resistance, must be understood and addressed to improve control and prevention strategies.